ON PRECISION ACOUSTIC WAVE CALCULATION IN A FREQUENCY DOMAIN - Tomasz Rymarczyk; Jan Sikora (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The accuracy of the calculation of acoustic problems formulated in the frequency domain is presented in this work. The issues of the acoustic point sources modelling were discussed and the influence of frequency as well as the impact of the geometry of the analysed area on the accuracy of calculations were indicated. Speaking about the influence of geometry, we mean not only discretization but also the configuration of the considered area, such as for example point sources localization close to the outer edge.